2017
DOI: 10.1002/andp.201700211
|View full text |Cite
|
Sign up to set email alerts
|

Holographical Aspects of Dyonic Black Holes: Massive Gravity Generalization

Abstract: The content of this paper includes studying holographical and thermodynamical aspects of dyonic black holes in the presence of massive gravity. For the first part of paper, thermodynamical properties of the bulk which includes black holes are studied and the main focus is on critical behavior. It will be shown that the existence of massive gravitons introduces remnant for temperature after evaporation of black holes, van der Waals phase transition for non-spherical black holes and etc. The consistency of diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 166 publications
(180 reference statements)
0
32
0
Order By: Relevance
“…Meanwhile, the existence of M Q Q results in the presence of divergencies for the Ricci scalar, which are not consistent with any phase transition point. Recently, by several studies it was shown that it is possible for the mass of the black holes to have root(s) [106,107]. This indicates that, for this form of the Quevedo metric, the existence of M and its roots may provide the possibility of the existence of divergencies in its Ricci scalar which are not matched with any phase transition point.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
“…Meanwhile, the existence of M Q Q results in the presence of divergencies for the Ricci scalar, which are not consistent with any phase transition point. Recently, by several studies it was shown that it is possible for the mass of the black holes to have root(s) [106,107]. This indicates that, for this form of the Quevedo metric, the existence of M and its roots may provide the possibility of the existence of divergencies in its Ricci scalar which are not matched with any phase transition point.…”
Section: Geometrical Thermodynamicsmentioning
confidence: 99%
“…Moreover, the bi-gravity extension of the solution was found in [13] which covers the previously known spherically symmetric solutions (see [14][15][16] for reviews on black holes in massive gravity). Recently, other extensions of the dRGT massive gravity solution were explored [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The super-conductivity was investigated by considering AdS/CFT duality [16]. Thermodynamics of dyonic BH, phase transitions and critical phenomena were studied in [17], [18]. All these shows the importance of dyonic BH solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In [32]- [44] NED's coupled to general relativity (GR) were investigated. Thermodynamics of BH was studied in [18]- [52]. Electric and magnetic charged BHs were investigated in the framework of NED in [53]- [61].…”
Section: Introductionmentioning
confidence: 99%